Novel genetic polymorphisms identified in the clinical isolates of Mycobacterium tuberculosis PE_PGRS33 gene modulate cytokines expression and promotes survival in macrophages - Rahul Gupta; Manitosh Pandey; Amit Kumar Pandey; Pramod Kumar Tiwari; Rabbind Singh Amrathlal (Elsevier, 2022)
Objective: PE_PGRS33 is a member of multi-gene family restricted to pathogenic Mycobacteria and their functions remain elusive. PE_PGRS33 is highly polymorphic in nature to evade host's immune response. Therefore, we investigated PE_PGRS33 gene polymorphisms in clinical isolates and functional characterization using in vitro experiments. Methods: A total of 103 clinical isolates were recruited. Genomic DNA was extracted, PE_PGRS33 gene amplification, sequencing. Afterward, we have cloned, expressed PE_PGRS33 wild type and three polymorphic alleles in M. smegmatis. Further, performed in vitro stresses assays, THP-1 differentiated macrophage infection assays followed by quantification of cytokine expression. Results: We have identified nine novel polymorphisms and also demonstrated that in comparison to M. smegmatis expressing wild type/Mut_alleles displayed altered in growth kinetics and colony morphology. M. smegmatis harbouring Mut_allele3 survived better under oxidative, acidic stress and were resistant to lysozyme treatment. qRT-PCR of cytokines TNF-α, IL-12 and IL-10 after infection with recombinant M. smegmatis showed two Mut_allele (Mut_allele1 and Mut_allele3) induced higher expression of TNF-α, IL-12, while IL-10 expression was decreased in both mutant alleles as compared to wild type PE_PGRS33 at each experimental time point. Conclusion: Results of our functional study suggest that PE_PGRS33 gene polymorphisms aid in the survival or persistence of M. tuberculosis and differentially modulate the expression of various cytokines. Overall this study suggests that Mtb clinical strains harbouring different PE_PGRS33 alleles could act as a virulence determinant by differentially regulating pathways essential for the pathogen's ability to adapt inside the host.